Tomato (Lycopersicon esculentum) supplementation induces changes in cardiac miRNA expression, reduces oxidative stress and left ventricular mass, and improves diastolic function - Pereira, Bruna L. B. [UNESP]; Arruda, Fernanda C. O. [UNESP]; Reis, Patrícia P. [UNESP]; Felix, Tainara F. [UNESP]; Santos, Priscila P. [UNESP]; Rafacho, Bruna P. [UNESP]; Gonçalves, Andrea F. [UNESP]; Claro, Renan T. [UNESP]; Azevedo, Paula S. [UNESP]; Polegato, Bertha F. [UNESP]; Okoshi, Katashi [UNESP]; Fernandes, Ana A. H. [UNESP]; et al. (MDPI, 2015)
The aim of this study was to evaluate the effects of tomato supplementation on the normal rat heart and the role of oxidative stress in this scenario. Male Wistar rats were assigned to two groups: a control group (C; n = 16), in which animals received a control diet + 0.5 mL of corn oil/kg body weight/day, and a tomato group (T; n = 16), in which animals received a control diet supplemented with tomato +0.5 mL of corn oil/kg body weight/day. After three months, morphological, functional, and biochemical analyses were performed. Animals supplemented with tomato had a smaller left atrium diameter and myocyte cross-sectional area (CSA) compared to the control group (C group: 474 (415–539); T group: 273 (258–297) µm2; p = 0.004). Diastolic function was improved in rats supplemented with tomato. In addition, lipid hydroperoxide was lower (C group: 267 ± 46.7; T group: 219 ± 23.0 nmol/g; p = 0.039) in the myocardium of rats supplemented with tomato. Tomato intake was also associated with up-regulation of miR-107 and miR-486 and down-regulation of miR-350 and miR-872. In conclusion, tomato supplementation induces changes in miRNA expression and reduces oxidative stress. In addition, these alterations may be responsible for CSA reduction and diastolic function improvement.
Keywords: Hypertrophy; MicroRNA; Oxidative stress; Tomato